Performer, Reporter, and Marketer: Three Different Local Parliament Faces on Social Media - Zailani Surya Marpaung; Anang Dwi Santoso (Policy & Governance Review, 2019)
Indonesian local parliaments have an image as a corrupt, closed, outdated, and unreachable institution in the public’s eyes. However, the parliaments have never tried to more actively developing policies which encourage active community participation. The recent adoption of social media by local parliaments seems to be a sign of the parliament’s willingness to encourage greater community contributions. However, little can be understood about the implications of these activities. Moreover, whether social media contributes significantly to community participation in local parliaments. The purpose of this study is to explore the use of social media by local parliaments. This study employed qualitative multiple case studies by conducting a content analysis on Facebook and Twitter in four local parliaments. This study found three faces of local parliaments on social media which are performers, reporters, and marketers. In general, there has been a willingness of local parliaments to become more transparent and participatory institutions. Nevertheless, the massive adoption of social media to promote more participatory democratic practices was conducted half-heartedly by the local parliaments. Practically, if local parliaments want to use social media to enchance their image, they must publish content that promotes openness such as online assembly and educative information.